Awareness, knowledge, disease prevention practices, and immunization attitude of hepatitis E virus among food handlers in Klang Valley, Malaysia - Sakshaleni Rajendiran; Wong Li Ping; Yuvaneswary Veloo; Syahidiah Syed Abu Thahir (Taylor & Francis Group, 2024)
ABSTRACTConcern about the zoonotic Hepatitis E virus (HEV) is rising. Since, food handlers are at greater risk in contracting HEV, the present study aims to determine awareness, knowledge, prevention practices against HEV, and immunization attitudes. A cross sectional study was conducted among 400 food handlers in Klang Valley, Malaysia from December 2021 to March 2022. A structured questionnaire was employed for data collection and analysis with Statistical Package for Social Science (SPSS) version 29. Approximately 4.5% of the respondents (18) reported having heard of HEV, while the median scores for the knowledge and practice domains were 0/10 and 1/5, respectively. A total of 316 (79%) respondents expressed willingness to obtain vaccination if made available. This study also found that those respondents who completed their tertiary education were significantly possessed better knowledge of the disease [odd ratio (OR) = 8.95, and 95% confidence interval (CI) 4.98-16.10]. Respondents with HEV awareness reported considerably better practices (OR = 8.24, 95% CI 1.72-39.63). Food handlers with one to five years of experience in the industry expressed notable willingness to take vaccination (OR = 7.71, 95% CI 1.79-33.18). Addressing poor HEV awareness and knowledge and poor practices against the disease is crucial in enlightening the policy makers about awareness among food handlers and general population. Nonetheless, a good immunization attitude, significant acceptance toward vaccination even with the vaccine being unavailable in Malaysia, and limited awareness of HEV highlight a promising development.